Analysis of Patient Satisfaction at the Ngudi Sehat Clinic Manang Baki Sukoharjo - Wulan, Arum Sekar; Sudarwati, Sudarwati; DPW, Ida Aryati (Innovative: Journal Of Social Science Research, 2024)
Analysis of the Influence of Service Quality on Patient Satisfaction at the Ngudi Sehat Manang Baki Sukoharjo Clinic. This research aims to determine and explain the influence of Service Quality consisting of Reliability, Guarantee, Physical Evidence, Empathy and Responsiveness on Patient Satisfaction at the Ngudi Waras Manang Baki Sukoharjo Clinic. The population of this study was all 257 patients of the Ngudi Sehat Manang Baki Sukoharjo Clinic in 2023 with a sample of 125 people using the Ferdinad formula. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that service quality has a positive and significant effect on patient satisfaction at the Ngudi Sehat Manang Baki Sukoharjo Clinic. Physical evidence contributed to patient satisfaction by 97%, while the remaining 3% was explained by other variables not proposed in this study. The suggestion from this research is that the Ngudi Sehat Manang Baki Sukoharjo Clinic needs to improve all dimensions of service quality so that patient satisfaction can increase.